Late‐Stage Modification of Aminoglycoside Antibiotics Overcomes Bacterial Resistance Mediated by APH(3') Kinases. Issue 36 (17th May 2022) - Bastian, Andreas A.; Bastian, Maria; Jäger, Manuel; Loznik, Mark; Warszawik, Eliza M.; Yang, Xintong; Tahiri, Nabil; Fodran, Peter; Witte, Martin D.; Thoma, Anne; Köhler, Jens; Minnaard, Adriaan J.; et al.
Abstract: The continuous emergence of antimicrobial resistance is causing a threat to patients infected by multidrug‐resistant pathogens. In particular, the clinical use of aminoglycoside antibiotics, broad‐spectrum antibacterials of last resort, is limited due to rising bacterial resistance. One of the major resistance mechanisms in Gram‐positive and Gram‐negative bacteria is phosphorylation of these amino sugars at the 3'‐position by O ‐phosphotransferases [APH(3')s]. Structural alteration of these antibiotics at the 3'‐position would be an obvious strategy to tackle this resistance mechanism. However, the access to such derivatives requires cumbersome multi‐step synthesis, which is not appealing for pharma industry in this low‐return‐on‐investment market. To overcome this obstacle and combat bacterial resistance mediated by APH(3')s, we introduce a novel regioselective modification of aminoglycosides in the 3'‐position via palladium‐catalyzed oxidation. To underline the effectiveness of our method for structural modification of aminoglycosides, we have developed two novel antibiotic candidates overcoming APH(3')s‐mediated resistance employing only four synthetic steps. Abstract : Regioselective oxidation : A scalable catalytic alcohol oxidation of structurally complex 4, 5‐ and 4, 6‐disubstituted aminoglycoside antibiotics is reported. Exploiting a palladium catalyst, this late‐stage modification is extremely selective tackling only the hydroxyl group in 3′‐position. Subsequent modification of the resulting ketone derivatives enables facile access to novel antibiotic candidates, in only four synthetic steps, which overcome bacterial resistance mediated by APH(3')s.